The Influence of the Application of Discovery Learning on the Achievement of Class X Students of Raudlatul Falah High School - Bayu Pradana; Fathor Rakhman; Yesi Puspitasari (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of the application of discovery learning on student achievement in class X SMA Raudlatul Falah in Indonesian history subjects. This research is a type of quantitative descriptive research with teacher respondents. Data collection techniques in this study were observation, interviews and documentation which were then analyzed in each data collection. Based on the results of these studies indicate that it greatly increases student achievement